Problematika Pengelolaan Pendapatan Asli Daerah di Era Otonomi Daerah - Lukman Santoso (UIN Sunan Kalijaga Yogyakarta, 2013)
The post-reform era of regional autonomy, has brought major changes in the state system. Included in the financial management system and mechanism of local government. In the context of autonomy, in addition to the transfer of central, local governments are required to have their own sources of funding in the form of local revenue (PAD), lending area, as well as other legitimate reception area. However, in practice, in the majority of the transfer region of the Central Government is the main source of local government funding to finance daily operations, which by the local government